Service quality of integrated Antenatal Care (ANC) and pregnant women participation on Human Immunodeficiency Virus (HIV) tests - Asni Asni; Mochamad Anwar; Sulistyaningsih Sulistyaningsih (Journal of Health Technology Assessment in Midwifery, 2018)
WHO data in 2016 estimated that 36.7 million people suffered from HIV globally, and 34.5 million among them were adults. Yogyakarta Special Province in 2016 found that there were 2,954 cases of HIV with the highest cases in Sleman Regency as many as 868 cases. Mlati I Primary Health Center was a Primary Health Center with the lowest coverage of HIV testing for pregnant women, namely in 2017 there were 752 pregnant women, and only 414 (55.05%) were tested for HIV. The purpose of this study was to determine the relationship between perceptions of integrated antenatal care quality service and the participation of HIV testing of pregnant women. The study applied cross sectional research method. The population in this study were pregnant women who performed ANC examinations at Mlati I Primary Health Center in September - November 2018 with a total of 318 pregnant women. The samples in the study were 154 with the simple random sampling technique. The instrument of data collection in this study used a questionnaire. Data analysis employed chi Square and logistic regression. The results of bivariate statistical tests using chi square showed that sig value = 0.000 0.05 with OR 13.896 meaning that women who had a good perception of the quality of ANC services had 13.896 higher chance to have HIV tests compared to those who had poor perceptions of the quality of integrated ANC services . Good perception of the quality of integrated ANC services for pregnant women had a greater chance of taking an HIV test.